2016
DOI: 10.2135/cropsci2016.04.0219
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Combining Ability and Genotype‐By‐Environment Interaction of Quality Protein Maize Inbred Lines Adapted to Tropical‐Highlands

Abstract: Production of quality protein maize (Zea mays L., QPM) is an economic and sustainable approach that can help to alleviate protein deficiency in developing countries. However, QPM cultivars with high grain yield and wide adaptation to the tropical‐highland subhumid maize agroecologies are yet to be developed and released for farmers. The objectives of this study were, therefore, to determine the magnitude of heterosis and combining ability of elite QPM inbred lines and to establish the genotype‐by‐environment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 39 publications
5
7
1
Order By: Relevance
“…In combine analysis across environments, significant GCA and SCA mean squares were observed for the trait (Table 4). In agreement with the present results, Kanagarasu et al (2010) and Abakemal et al (2016) reported significant mean squares due to GCA and SCA for thousand-kernel weight.…”
Section: Combining Ability Analysessupporting
confidence: 93%
See 3 more Smart Citations
“…In combine analysis across environments, significant GCA and SCA mean squares were observed for the trait (Table 4). In agreement with the present results, Kanagarasu et al (2010) and Abakemal et al (2016) reported significant mean squares due to GCA and SCA for thousand-kernel weight.…”
Section: Combining Ability Analysessupporting
confidence: 93%
“…level of variation for various characteristics, which makes selection possible for improved grain yield and agronomic traits under low N stress and non-stress conditions. Similar results have been reported (Dagne, 2008;Amare et al, 2016;Abakemal et al, 2016;Bullo and Dagne, 2016;Keno et al, 2017;Mafouasson et al, 2017).…”
Section: Line Code Pedigreesupporting
confidence: 86%
See 2 more Smart Citations
“…Growing season was the most important environmental factors affecting performance of this corn populations. The large effects of the environment have also been reported in quality protein maize for yield [43] and flowering traits [44]. The effect of environment also affected anthocyanin content, antioxidant activity in corn cobs [45], total anthocyanin content and total phenolic content in husk, cob, silk and tassel in purple waxy corn [46].…”
Section: Analysis Of Variancementioning
confidence: 99%